Crescimento de Pinus taeda L. em diferentes espaçamentos - Lima, Rodrigo (2010)
The objective of this research was to study the growth of Pinus taeda L. in different spacings. In the year 2002 a field experiment was installed in Irati, Parana State, with seedlings from clonal seed orchard. We used a randomized block design with five replicates of nine treatments, which simulate growing spaces between 1.0 m² and 16.0 m². The size of the plot tracks the number of trees is determined by the spacing of planting. 25 seedlings were selected in each treatment performing follow-up of growth of these annually. It was measured the total height of the plants between the years 2003 and 2009 and the diameter at breast height - 1.3 m (dbh) between 2006 and 2009. The effect of spacing in the growth of variable height, dbh, transversal area, basal area, volume per tree and per hectare was estimated by Bartlett`s test, analysis of variance, Tukey test and linear correlation coefficient of Pearson. Were calculated the increments of growth variables for assessment of its evolution. The main results were: height growth was not affected by vital spacings, except in the seventh year when it proved-was a difference between averages. The growth in dbh, transversal area, basal area, volume per tree and per hectare was influenced by growing spaces. Significant relationships between growth variables and those with the spacings. The evolution of the increment and current annual average of total height, dbh, transversal area, basal area, volume per tree and per hectare was affected by the growing space. In general, was confirmed the influence of spacing in the growth of Pinus taeda L, up to 7 years of age. There is a need for thinning the spacings of 1.0 and 2.0 m² as a measure to reduce competition between trees expanding the space available for their full development.